Critical analysis about the use of icts in the english language learning process - Almeida Burbano, Samuel Esteban (2023)
The use of Information and Communication Technologies (ICTs) in the teaching-learning process has gained relevance due to the increasing digitization. The problem arises because it has not been possible to discern the type of use that ICTs have in the educational process. Therefore, this research aimed to analyze the use of ICTs in the English language learning process in second grade classes A, B, H, I and J at the IEF "Benito Juárez" during the 2022 academic year 2023. The use of a qualitative approach methodology and a descriptive method have been used. For data collection, an interview guide and a survey were designed, each with 10 questions related to the use of ICT for learning English. Likewise, 4 English teachers and 124 students participated in the study, who were selected using a non-probabilistic convenience sample. While for the analysis and discussion of the unstructured interview guide a Thematic Analysis method was applied. or the survey a technique of tabulating percentages on a Likert scale was obtained. The main results show that there are several challenges in the use of ICT, since teachers do not use the technology frequently due to the lack of technological resources, inadequate infrastructure, and little government investment in education. However, most of the participants agreed that it would be useful to use ICT to learn English. In conclusion, ICTs represent great opportunities to improve the teaching of English and at the same time a series of challenges that must be overcome to achieve meaningful learning in the digital age